Effects of Cool-Down Exercise and Cold-Water Immersion Therapy on Basic Fitness and Sport-Specific Skills among Korean College Soccer Players - Yoon-Hyung Lee; Jin Ho Yoon; Ki-Jae Song; Jae-Keun Oh (Tehran University of Medical Sciences, 2021)
Background: We aimed to examine the effects of cool-down exercise and cold-water immersion therapy on agility, speed, power, balance, and sport-specific skill performance in college soccer players, and to provide baseline data for the development of effective recovery programs. Methods: In August 2020, 21 male college soccer players in Seoul, Korea, were randomly divided into the following groups: control group (CG, n=7), cool-down exercise group (CDG, n=7), and cool-down exercise plus cold-water immersion group (CDCWG, n=7). Agility, speed, power, balance, and sport-specific skill performance were assessed before and after the intervention. Results: No significant differences in Southeast Missouri (SEMO) Agility Test, 20-m sprint test, vertical jump test, or Y-balance test (right) were observed among the groups; however, there was a significant effect of time (P<0.05) and a significant time × group interaction (P<0.05). Significant effects of time (P<0.001), group (P=0.043), and a time × group interaction (P=0.009) were observed in the Y-balance test (left). There were no between-group differences in the 22-m dribble test, shooting test (left), or shooting test (right); however, there were significant effects of time (P<0.05) and significant time × group interactions (P<0.05). No significant effects of group or time × group interactions were observed for the kicking test (left or right); however, there were significant effects of time (P<0.001). Conclusion: Addition of cold-water immersion therapy to a recovery program including cool-down exercise can promote recovery of basic and sport-specific abilities among college soccer players.